APPLICATION INTEGRATION METHODS ON LANDSAT ETM + TO DETERMINE EARTHQUAKE POTENTIALS IN PALU GRABEN - M. Rusydi H; Hartono Hartono; M. Pramono Hadi; Sunarto Sunarto (Faculty of Geography, Universitas Gadjah Mada, 2010)
This study aims to assess the ability of the integration method at LandsatETM + imagery in recognizing object fault, main fault and secondary fault in PaluGraben. Mapping of fault and calculate earthquake potential, based of fault that isfound in Graben of Palu. The image used in this study is Landsat ETM +.Techniques used to process Landsat ETM + is a method of integration. LandsatETM+ imagery processed with ENVI software 4.4, while the mapping of faults anddetermining of length using ArcGIS 9.2.The potential of earthquakes is calculatedfrom the length of faults found in the Graben of Palu. Results obtained showed thatthe patterns of lineament as a picture of fault in the Palu Graben can be extractedfrom Landsat ETM +. Lineament of fault is seen clearly on Landsat ETM + imageprocessed with integration method and band combination, 45PC1_8. Faults arearranged in the form of map. There are 66 faults found at research sites.Magnitude earthquake 5,5 SR can be produced from the fault with a length greaterthan or equal to 9 km. If each faults contributes the same to earthquakeoccurrence, the potential incidence of earthquake with magnitude greater than orequal to 5.5 SR in the Graben of Palu is 33.8%, while the magnitude is smallerthan 5.5 SR is 66.2%. The largest magnitude that can occur in Palu Graben, 7.1SR. These results indicate that the potential earthquake destructive (≥ 5.5 SR) ofapproximately 33.8%.